Minimum habitat thresholds required for conserving mountain lion genetic diversity. Issue 19 (1st September 2020) - Dellinger, Justin A.; Gustafson, Kyle D.; Gammons, Daniel J.; Ernest, Holly B.; Torres, Steven G.
Abstract: Jointly considering the ecology (e.g., habitat use) and genetics (e.g., population genetic structure and diversity) of a species can increase understanding of current conservation status and inform future management practices. Previous analyses indicate that mountain lion ( Puma concolor ) populations in California are genetically structured and exhibit extreme variation in population genetic diversity. Although human development may have fragmented gene flow, we hypothesized the quantity and quality of remaining habitat available would affect the genetic viability of each population. Our results indicate that area of suitable habitat, determined via a resource selection function derived using 843, 500 location fixes from 263 radio‐collared mountain lions, is strongly and positively associated with population genetic diversity and viability metrics, particularly with effective population size. Our results suggested that contiguous habitat of ≥10, 000 km 2 may be sufficient to alleviate the negative effects of genetic drift and inbreeding, allowing mountain lion populations to maintain suitable effective population sizes. Areas occupied by five of the nine geographic–genetic mountain lion populations in California fell below this habitat threshold, and two (Santa Monica Area and Santa Ana) of those five populations lack connectivity to nearby populations. Enhancing ecological conditions by protection of greater areas of suitable habitat and facilitating positive evolutionary processes by increasing connectivity (e.g., road‐crossing structures) might promote persistence of small or isolated populations. The conservation status of suitable habitat also appeared to influence genetic diversity of populations. Thus, our results demonstrate that both the area and status (i.e., protected or unprotected) of suitable habitat influence the genetic viability of mountain lion populations. Abstract : We report a strong relationship between amount of habitat and genetic diversity in a charismatic umbrella species. We also demonstrate habitat thresholds needed to maintain genetic integrity of the species. Our work defines current conservation needs and adds to general ecological theory concerning genetic diversity and amount of available habitat.